Phytochemical Screening and in Vitro Antimicrobial Activities of Euphorbia Lateriflora on Selected Pathogens - Falana, Mansurat B.; Nurudeen, Quadri O. (Iraqi Journal of Science, 2022)
Euphorbia lateriflora is a popular traditional medicinal plant whose leaves are used in Africa, especially Nigeria, to treat wounds and many diseases. This study investigated the preliminary phytochemical constituents, secondary metabolites by High-Performance Liquid Chromatography “HPLC” technique, and antimicrobial potentials (Minimum Inhibitory Concentration “MIC”, Minimum Fungicidal Concentration “MFC” and disc diffusion assay) of various concentrations (100 mg/mL, 50 mg/ml, and 25 mg/mL) of the solvents (ethyl acetate and n-hexane) extracts of E. lateriflora against Staphylococcus aureus, Escherichia coli and Candida albicans. The phytochemical screening revealed that out of the thirteen constituents screened for, n-hexane extract contained seven components, including flavonoids, coumarin, steroid, glycosides, triterpenes, terpenoids, and alkaloids. In contrast, the ethyl acetate extract contains saponin, flavonoids, coumarin, steroid, glycosides, triterpenes, terpenoids, and alkaloids. The HPLC chromatogram of n-Hexane and ethyl acetate extracts of E. lateriflora detected numerous unidentified compounds along with a potential antimicrobial compound identified as caffeic acid. The low MIC (6.25 - 50 mg/mL), shown by the n-hexane extract signified a greater antimicrobial activity than ethyl acetate extract. This was further implicated by the varying concentrations levels, rather than the strain-dependent zone of inhibitions obtained. The highest diameter of zone of inhibition (14.23 mm) was obtained at 100 mg/mL by n-hexane extract against E. coli and S. aureus, respectively, while the lowest zone of inhibition (6.00 mm) was obtained by n-hexane at 25 mg/mL concentrated tested against S. aureus. However, the diameter of the zone of inhibition of Ciprofloxacin (50 mg/mL) ranged between 10-16 mm for E. coli and 6-10 mm for S. aureus. At the same time, 14.00 mm was obtained by itraconazole (antifungal agent) against C. albicans. Thus, this study shows that E. lateriflora harbors active compounds and supports the claim that its extract may be effective against infections caused by the test organisms, as practiced for years among rural dwellers in Nigeria.